2000
DOI: 10.1091/mbc.11.8.2673
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for the Yeast Phosphatidylinositol 4-Kinases, Stt4p and Pik1p, in Secretion, Cell Growth, and Organelle Membrane Dynamics

Abstract: The yeast Saccharomyces cerevisiae possesses two genes that encode phosphatidylinositol (PtdIns) 4-kinases, STT4 and PIK1. Both gene products phosphorylate PtdIns at the D-4 position of the inositol ring to generate PtdIns(4)P, which plays an essential role in yeast viability because deletion of either STT4 or PIK1 is lethal. Furthermore, although both enzymes have the same biochemical activity, increased expression of either kinase cannot compensate for the loss of the other, suggesting that these kinases reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
427
5
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(467 citation statements)
references
References 59 publications
29
427
5
6
Order By: Relevance
“…The mammalian ortholog of STT4 is PtdIns4KIII␣ (251,391) and the ortholog of PIK1 is PtdIns4KIII␤ (12,233,250). In yeast, STT4 and PIK1 do not compensate for each other in deletion studies, with STT4 functioning in regulation of the actin cytoskeleton and PIK1 essential for membrane traffic (9,129,370). PtdIns4KIII␤ has been localized to the Golgi, a location consistent with the work on yeast PIK1 (120,392).…”
Section: B Ptdins 4-kinasessupporting
confidence: 60%
“…The mammalian ortholog of STT4 is PtdIns4KIII␣ (251,391) and the ortholog of PIK1 is PtdIns4KIII␤ (12,233,250). In yeast, STT4 and PIK1 do not compensate for each other in deletion studies, with STT4 functioning in regulation of the actin cytoskeleton and PIK1 essential for membrane traffic (9,129,370). PtdIns4KIII␤ has been localized to the Golgi, a location consistent with the work on yeast PIK1 (120,392).…”
Section: B Ptdins 4-kinasessupporting
confidence: 60%
“…Similarly, we found that overexpression of PIK1 could restore the sporulation of sec14-1 diploids to near wild-type frequency, and suppression of the meiotic defect was dependent on Spo14p (Table 2, lines 19 -20). In contrast, overexpression of the other PtdIns 4-kinase isoform, Stt4p, which supplies PtdIns(4)P primarily at the plasma membrane (Audhya et al, 2000), was unable to suppress the sporulation defect of sec14-1 cells (Table 2, line 21). These results support the hypothesis that PtdIns delivery is an essential function of Sec14p for spore formation and suggest that it is specifically the pool of PtdIns(4)P available at the Golgi that is critical.…”
Section: Suppression Of Sec14 Sporulation Defect By Overexpression Ofmentioning
confidence: 99%
“…Exit of secretory proteins from the Golgi requires the function of Sec14p, a PtdIns/PtdCho transfer protein (Bankaitis et al, , 1990, and Pik1p, a PtdIns 4-kinase, which phosphorylates PtdIns to synthesize PtdIns(4)P (Hama et al, 1999;Walch-Solimena and Novick, 1999;Audhya et al, 2000). Consequently, SEC14 and PIK1 are essential genes in vegetatively growing cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutants with defects in PI(4)P production by these lipid kinases showed reduced secretion, delayed vacuolar transport, defective protein retrieval from endosomes to the Golgi, and aberrant Golgi morphology (Godi et al, 1999;Hama et al, 1999;Walch-Solimena and Novick, 1999;Audhya et al, 2000). Recent work, mainly in mammalian cells, has revealed effectors of phosphatidylinositol 4-phosphate [PI(4)P] such as the PI(4)P adaptor proteins FAPP1 and FAPP2, which are involved in the generation of transport carriers for exocytosis (Godi et al, 2004;Vieira et al, 2005) and the clathrin adaptor AP-1 (Wang et al, 2003;Heldwein et al, 2004) that participates in the formation of clathrin-coated vesicles.…”
Section: Introductionmentioning
confidence: 99%